Critical Evaluation on Structural Stiffness of Porous Cellular Structure of Cobalt Chromium Alloy - N. M. S., Abd Malek; S. R., Mohamed; S. A., Che Ghani; W. S., Wan Harun (IOP Publishing Ltd, 2015)
In order to improve the stiffness characteristics of orthopedic devices implants that mimic the mechanical behavior of bone need to be considered. With the capability of Additive layer manufacturing processes to produce orthopedic implants with tailored mechanical properties are needed. This paper discusses finite element (FE) analysis and mechanical characterization of porous medical grade cobalt chromium (CoCr) alloy in cubical structures with volume based porosity ranging between 60% to 80% produced using direct metal laser sintering (DMLS) process. ANSYS 14.0 FE modelling software was used to predict the effective elastic modulus of the samples and comparisons were made with the experimental data. The effective mechanical properties of porous samples that were determined by uniaxial compression testing show exponential decreasing trend with the increase in porosity. Finite element model shows good agreement with experimentally obtained stress-strain curve in the elastic regions. The models prove that numerical analysis of actual prosthesis implant can be computed particularly in load bearing condition